Mapping Priority of Policy Program in Value Chain Operation for Sustainability Indonesia Palm Oil Industry - Fathurahman, Heri; Sundram, Veera Pandiyan Kaliani; Nugroho, Bernardus Yuliarto; Muhamed, Ariff Azly (Journal of Ecohumanism, 2025)
One of the problems faced by Indonesia as the main exporter of palm oil today is that most of Indonesia's palm oil exports are still in the form of raw materials with low selling value. In facing these various challenges, various policy supports are needed, including (1) increasing the productivity of people's oil palm plantations through a replanting program, (2) providing certified oil palm seeds, (3) increasing financial access for people's farmers through a people's land certification program, (4) increasing added value through downstream, (5) price stabilization through increasing domestic and regional markets, (6) investment and trade diplomacy and cooperation, (7) improving infrastructure and trade facilitation, (8) data and information, and (9) strengthening farmer and business actor organizations. This dynamic situation also causes system variations over time. Therefore, a study is needed regarding Mapping Priority of Policy Program in Value Chain Operation for Sustainability of the Indonesian Palm Oil Industry. The research method used is a quantitative method with data collection by distributing web-based questionnaires to experts in the palm oil industry in Indonesia with samples that are adjusted and match the Fuzzy VIKOR technique and Fuzzy TOPSIS technique. A web-based questionnaire was developed for data collection, which was then distributed to thirty experts. From the comparison results between Fuzzy VIKOR and Fuzzy TOPSIS, there are almost similarities in determining the priority of policy program in upstream operations value chain, midstream operations value chain and downstream operations value chain as follows. As for in upstream operations value chain namely the first rank of Fuzzy VIKOR and Fuzzy TOPSIS is the same, namely the priority of policy program is Environment. As for in midstream operations value chain namely the first rank of Fuzzy VIKOR is Governance whereas the first rank Fuzzy TOPSIS is Environment. As for in downstream operations value chain namely the first rank of Fuzzy VIKOR is Economics and the first rank of Fuzzy TOPSIS is Social.